2007
DOI: 10.1002/bdrc.20091
|View full text |Cite
|
Sign up to set email alerts
|

Genetic analysis of molecular oscillators in mammalian somitogenesis: Clues for studies of human vertebral disorders

Abstract: The repeating pattern of the human vertebral column is shaped early in development, by a process called somitogenesis. In this embryonic process, pairs of mesodermal segments called somites are serially laid down along the developing neural tube. Somitogenesis is an iterative process, repeating at regular time intervals until the last somite is formed. This process lays down the vertebrate body axis from head to tail, making for a progression of developmental steps along the rostral-caudal axis. In this review… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 105 publications
(103 reference statements)
0
5
0
Order By: Relevance
“…Somitogenesis is a complex and vital process in vertebrate development that involves many known genes distributed across several families of signaling proteins, and a vast amount of work has been done to characterize this process (see reviews: Stickney et al, 2000; Pourquié, 2001; Aulehla and Herrmann, 2004; Sewell and Kusumi, 2007; Geetha‐Loganathan et al, 2008; Dunwoodie, 2009). To our knowledge, there are currently no chromatin remodelers reported to play a role in somitogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Somitogenesis is a complex and vital process in vertebrate development that involves many known genes distributed across several families of signaling proteins, and a vast amount of work has been done to characterize this process (see reviews: Stickney et al, 2000; Pourquié, 2001; Aulehla and Herrmann, 2004; Sewell and Kusumi, 2007; Geetha‐Loganathan et al, 2008; Dunwoodie, 2009). To our knowledge, there are currently no chromatin remodelers reported to play a role in somitogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…A case-control study identified the association of variants of Raldh1A2, Cyp26A1, and CRABP1 retinoic genes and neural tube defects in humans ( 230 ). Experimental studies on mouse models have shown that overexpression of retinoic acid leads to neural tube defects ( 236 , 237 ). A recent study found that treatment of neural crest cells (NSCs) with all-trans-retinoic acid culminates in neural tube deformities ( 238 ).…”
Section: Signaling Pathways—neural Tube Defectsmentioning
confidence: 99%
“…All-trans retinoic acid (atRA) is a normal metabolite of retinoic acid present in the body and is an important factor in embryonic development (11). Previous studies have reported that excess atRA leads to the occurrence of NTDs (12,13). However, its specific molecular mechanism remains to be elucidated.…”
Section: Effect Of Notch1 On Neural Tube Defects and Neural Stem Cell...mentioning
confidence: 99%